Controlling the physics and chemistry of binary and ternary praseodymium and cerium oxide systems. Issue 38 (10th September 2015) - Niu, Gang; Zoellner, Marvin Hartwig; Schroeder, Thomas; Schaefer, Andreas; Jhang, Jin-Hao; Zielasek, Volkmar; Bäumer, Marcus; Wilkens, Henrik; Wollschläger, Joachim; Olbrich, Reinhard; Lammers, Christian; Reichling, Michael
Abstract : Binary and ternary PrO x and CeO x films grown on Si(111) are most versatile systems available in a variety of stoichiometries and surface structures. Abstract : Rare earth praseodymium and cerium oxides have attracted intense research interest in the last few decades, due to their intriguing chemical and physical characteristics. An understanding of the correlation between structure and properties, in particular the surface chemistry, is urgently required for their application in microelectronics, catalysis, optics and other fields. Such an understanding is, however, hampered by the complexity of rare earth oxide materials and experimental methods for their characterisation. Here, we report recent progress in studying high-quality, single crystalline, praseodymium and cerium oxide films as well as ternary alloys grown on Si(111) substrates. Using these well-defined systems and based on a systematic multi-technique surface science approach, the corresponding physical and chemical properties, such as the surface structure, the surface morphology, the bulk–surface interaction and the oxygen storage/release capability, are explored in detail. We show that specifically the crystalline structure and the oxygen stoichiometry of the oxide thin films can be well controlled by the film preparation method. This work leads to a comprehensive understanding of the properties of rare earth oxides and highlights the applications of these versatile materials. Furthermore, methanol adsorption studies are performed on binary and ternary rare earth oxide thin films, demonstrating the feasibility of employing such systems for model catalytic studies. Specifically for ceria systems, we find considerable stability against normal environmental conditions so that they can be considered as a "materials bridge" between surface science models and real catalysts.